2011
DOI: 10.1016/j.bbi.2011.02.011
|View full text |Cite
|
Sign up to set email alerts
|

Detection of plasma autoantibodies to brain tissue in young children with and without autism spectrum disorders

Abstract: Autism spectrum disorders (ASDs) are characterized by impaired language and social skills, often with restricted interests and stereotyped behaviors. A previous investigation of blood plasma from children with ASDs (mean age = 5½ years) demonstrated that 21% of samples contained autoantibodies that reacted intensely with GABAergic Golgi neurons of the cerebellum while no samples from non-sibling, typically developing children showed similar staining (Wills et al., 2009). In order to characterize the clinical f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
34
3

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 29 publications
3
34
3
Order By: Relevance
“…The evidence strongly supports distinct roles for both maternal Croen et al, 2008b;Singer et al, 2008;Zimmerman et al, 2007) and patient (Henneberg et al, 1994;Libbey and Fujinami, 2010;Ryberg, 1982) autoantibodies in ASD, including an ability to affect structural brain development (Nordahl et al, 2013;Rossi et al, 2011). Offending antibodies of either origin appear to persist systemically for extended periods of time Piras et al, 2014;Singer et al, 2006;Zimmerman et al, 2007), and although there exists a correlation between the two there does appear to be at least some differences in effect (Piras et al, 2014).…”
Section: Anti-brain Antibodiesmentioning
confidence: 93%
“…The evidence strongly supports distinct roles for both maternal Croen et al, 2008b;Singer et al, 2008;Zimmerman et al, 2007) and patient (Henneberg et al, 1994;Libbey and Fujinami, 2010;Ryberg, 1982) autoantibodies in ASD, including an ability to affect structural brain development (Nordahl et al, 2013;Rossi et al, 2011). Offending antibodies of either origin appear to persist systemically for extended periods of time Piras et al, 2014;Singer et al, 2006;Zimmerman et al, 2007), and although there exists a correlation between the two there does appear to be at least some differences in effect (Piras et al, 2014).…”
Section: Anti-brain Antibodiesmentioning
confidence: 93%
“…A specific subgroup of GABAergic interneurons located in the V1 layer was identified as the specific target [194]. Controversially, another study suggested that this staining might be unspecific because immunoreactivity was detected using serum of both healthy controls and a ASD patient with the intriguing fact that the IgG seropositive ASD patients presented more severe behavior and emotional problems compared to the IgG seronegative ones [195].…”
Section: Autism Spectrum Disorder (Asd)mentioning
confidence: 99%
“…An important finding was reached by Wills research group (2009), they demonstrated that 21% the positive autoantibodies samples, reacted intensely with GABAergic Golgi neurons of the cerebellum while no samples from non-sibling, typically developing children showed similar staining (Wills et al, 2009). Further more, Rossi et al, (2011), demonstrated that 42% of controls and subjects with ASD were positively immunoreactive to some neural element, such as, cerebellar Golgi, interneurons, molecular layer of the dentate gyrus, and neuronal nuclei. Interestingly, children whose plasma reacted to brain tissue had scores on the Child Behavior Checklist (CBCL) that indicated increased behavioral and emotional problems.…”
Section: Cortical Connectivity In Autism Spectrum Disordersmentioning
confidence: 99%